Determinant factors of Perceived Risk-Based Maintenance Management (PRBMM) for public schools/ Nurul Diyana Mohd Dahari ... [et al.] - Mohd Dahari, Nurul Diyana; Mohammad Ali, Irwan; Khalil, Natasha; Abdul Wahab, Suriani Ngah (Universiti Teknologi MARA, Perak, 2024)
Maintenance is one of the key factors that keeps buildings safe and functional. However, there has been extensive research recently about the poor condition of public school facilities and the struggle to keep up with the demands of maintaining their timeworn school infrastructure. Perceived risk affects maintenance work decisions. This encompasses the perspectives of various stakeholders, such as the building's owner, facility managers, maintenance staff, and occupants, regarding the potential and impact of adverse occurrences resulting from maintenance practices. The problem addressed in this research is the absence of a comprehensive Perceive Risk-Based Maintenance Management (PRBMM) model for public schools. This research aims to identify the determinants of perceived risk in risk-based maintenance management. Numerous constructs from previous studies were used to create questionnaires. There were a total of 137 web-based self-administrative questionnaires that were distributed to technical experts who were in charge of the building maintenance of the public schools. The 137 sets were answered and completed. The data is then analysed using SPSS Statistics, Version 29. The findings suggest that the conceptual framework for this research consists of four determinant factors as independent variables, such as performance risk, financial risk, safety risk, and operational risk. Meanwhile, the responses perceive risk in risk-based maintenance management as a dependent variable.